Environmental influences on antibody-enhanced dengue disease outcomes - DINIZ, Daniel Guerreiro (2014)
Because an enriched environment (EE) enhances T-cell activity and T-lymphocytes contribute to immunopathogenesis during heterologous dengue virus (DENV) infections, we hypothesised that an EE increases dengue severity. To compare single serotype (SS) and antibody-enhanced disease (AED) infections regimens, serial intraperitoneal were performed with DENV3 (genotype III) infected brain homogenate or anti-DENV2 hyperimmune serum followed 24 h later by DENV3 (genotype III) infected brain homogenate. Compared AED for which significant differences were detected between the EE and impoverished environmental (IE) groups (Kaplan-Meyer log-rank test, p = 0.0025), no significant differences were detected between the SS experimental groups (Kaplan-Meyer log-rank test, p = 0.089). Survival curves from EE and IE animals infected with the AED regimen were extended after corticoid injection and this effect was greater in the EE than in the IE group (Kaplan-Meyer log-rank test, p = 0.0162). Under the AED regimen the EE group showed more intense clinical signs than the IE group. Dyspnoea, tremor, hunched posture, ruffled fur, immobility, pre-terminal paralysis, shock and death were associated with dominant T-lymphocytic hyperplasia and presence of viral antigens in the liver and lungs. We propose that the increased expansion of these memory T-cells and serotype cross-reactive antibodies facilitates the infection of these cells by DENV and that these events correlate with disease severity in an EE.